2021
DOI: 10.2131/jts.46.359
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cardiotoxicity assessment of BMS-986094, a guanosine nucleotide analogue, using human iPS cell-derived cardiomyocytes

Abstract: Predicting drug-induced side effects in the cardiovascular system is very important because it can lead to the discontinuation of new drugs/candidates or the withdrawal of marketed drugs. Although chronic assessment of cardiac contractility is an important issue in safety pharmacology, an in vitro evaluation system has not been fully developed. We previously developed an imaging-based contractility assay system to detect acute cardiotoxicity using human iPS cell-derived cardiomyocytes (hiPSC-CMs). To extend th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…Total RNA was isolated from MDA-MB-231 cells using TRIzol reagent (Thermo Fisher Scientific), and quantitative real-time reverse transcription (RT)-PCR was performed using the QuantiTect SYBR Green RT-PCR Kit (QIAGEN, Hilden, German) on an ABI PRISM 7900HT sequence detection system (Applied Biosystems, Foster City, CA, USA) as previously reported [40,41]. The relative change in the amount of transcript was normalized to the mRNA levels of glyceraldehyde-3-phosphate dehydrogenase (GAPDH).…”
Section: Qpcr Analysismentioning
confidence: 99%
“…Total RNA was isolated from MDA-MB-231 cells using TRIzol reagent (Thermo Fisher Scientific), and quantitative real-time reverse transcription (RT)-PCR was performed using the QuantiTect SYBR Green RT-PCR Kit (QIAGEN, Hilden, German) on an ABI PRISM 7900HT sequence detection system (Applied Biosystems, Foster City, CA, USA) as previously reported [40,41]. The relative change in the amount of transcript was normalized to the mRNA levels of glyceraldehyde-3-phosphate dehydrogenase (GAPDH).…”
Section: Qpcr Analysismentioning
confidence: 99%
“…Therefore, it could be concluded that BMS‐986094 has a chronical toxic effect on CMs based on changed calcium handling properties. In comparison, sofobuvir displayed only little to insignificant effects on calcium handling and contractility 21 . This underlines the potential of CM‐based 2D assays for toxicological screenings even regarding direct or chronical effects.…”
Section: Adherent Monolayer Cultivation Of Cardiomyocytesmentioning
confidence: 76%
“…In comparison, sofobuvir displayed only little to insignificant effects on calcium handling and contractility. 21 This underlines the potential of CM-based 2D assays for toxicological screenings even regarding direct or chronical effects.…”
Section: Adherent Monolayer Cultivation Of Cardiomyocytesmentioning
confidence: 84%
“…Real-Time PCR Quantitative PCR (qPCR) was performed according to previous protocol using a QuantiTect SYBR Green RT-PCR Kit (Qiagen, Valencia, CA, U.S.A.) with a QuantStudio 7 Flex Real-Time PCR System (Thermo Fisher Scientific). 9,10) The used primers were listed in Table 1. Each gene level was normalized by glyceraldehyde-3-phosphate dehydrogenase (GAPDH) using the ΔΔ Ct method.…”
Section: Methodsmentioning
confidence: 99%